The detection of cherry leaf-roll nepovirus and the use of molecular markers for germplasm identification in walnuts (Juglans regia L.) - Mkhize, Thokozani M (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.